A new species of Pachydema Laporte (Coleoptera: Scarabaeoidea: Scarabaeidae: Melolonthinae: Pachydemini) from the Canary Islands - Micó, Estefanía; Galante, Eduardo (Zootaxa, 2009)
Pachydema megalops sp. nov., a new species from Gran Canaria (Canary Islands, Spain) is described and illustrated. A key to all Canarian Pachydema Laporte species and illustrations of diagnostic structures are provided.